The effects of different antiembolic agents on the crystallinity of fractured bones during the healing period - Tunc, Burcu; Aksoy, Emin Emin; Usta, Metin; Üçişik, Ahmet Hikmet (Springer Verlag, 2009)
In order to decrease the potential clinical problems that could be caused by embolism Antiembolic agents are routinely used in orthopaedics& traumatology clinics, especially after arthroplastic operations or in case of having tumor and major trauma in order. This study was designed to evaluate the side effects of different antiembolic agents on the bone fracture healing. After experiments on animals, where "enoxaparin", "fondaparinux" and "heparin" are used as antiembolic agents given after bone fracture, fractured and healed bones are studied by using X-Ray Diffraction technique. To reach this idea, initially, rat which was used as experimental animal was injected by different antiembolic agents. After sacrificing (with the permission of ethical committee) of animal, XRD studies were performed on the bones in Material Laboratories of GYTE (Gebze Yuksek Technology Enstitusu) in order to reveal changes in the crystallinity of the bone samples. © 2021 Elsevier B.V., All rights reserved.
World Congress on Medical Physics and Biomedical Engineering: Image Processing, Biosignal Processing, Modelling and Simulation, Biomechanics -- Munich -- 81642
Keywords: Bone healing; Enoxaparin; Fondaparinux; Heparine; XRD